SnS / SnS / SnN co-doped graphene negative electrode material and preparation method thereof

By combining stannous sulfide with sulfur-nitrogen bidoped graphene to form a negative electrode material with a three-dimensional flexible structure, the problems of low graphite capacity and poor conductivity of stannous sulfide are solved, and high capacity and excellent rate performance are achieved.

CN114824185BActive Publication Date: 2025-02-07NANJING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110126795.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-01-29
Publication Date
2025-02-07
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, graphite has low theoretical capacity and cannot meet the needs of high capacity and high rate performance. At the same time, stannous sulfide has poor conductivity and volume expansion, which limits its application in negative electrode materials.

Method used

By combining stannous sulfide with sulfur-nitrogen bidoped graphene, suction filtration and high-temperature calcination, a three-dimensional flexible structure stannous sulfide/sulfur-nitrogen bidoped graphene negative electrode material is formed.

Benefits of technology

The conductive and electrochemical properties of the material are improved, high capacity and excellent cycle stability and rate performance are achieved, and the battery can still maintain a high capacity after 500 turns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824185B_ABST
    Figure CN114824185B_ABST
Patent Text Reader

Abstract

The present invention discloses a stannous sulfide / sulfur-nitrogen dual-doped graphene negative electrode material and a preparation method thereof. The present invention combines a method of suction filtration and high-temperature calcination to prepare a stannous sulfide / sulfur-nitrogen dual-doped graphene negative electrode material having a three-dimensional structure. The stannous sulfide / sulfur-nitrogen dual-doped graphene negative electrode material of the present invention has a high conductivity at 1A g ‑1 When the battery is charged and discharged under the current, the initial capacity reaches 1173mAh g ‑1 Even after 500 cycles, the battery capacity can still maintain 530mAh g ‑1 In the rate cycling test, the high current cycle returned to the initial 0.5A g ‑1 When cycling at low current, the battery capacity is still 503mAh g ‑1 , the first pseudocapacitance is as high as 93.9%, with excellent cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode materials and relates to a stannous sulfide / sulfur and nitrogen dual-doped graphene negative electrode material and a preparation method thereof. Background Art

[0002] In commercial lithium-ion batteries, the preparation technology of graphite as negative electrode material is very mature, and the capacity of lithium-ion batteries is mainly limited by the capacity of negative electrode materials. However, the theoretical capacity of graphite is low and cannot meet the rapid growth of people's demand for battery capacity and rate performance. Finding electrode materials with high capacity and high rate performance is the focus of future research. Compared with the theoretical capacity of graphite, which is only 372mAh g -1 SnS not only has 782mAh g -1 Theoretical capacity, and it can provide two active sites, tin and sulfur, during the lithium-ion battery cycle, which can increase the upper limit of the capacity of lithium-ion batteries. However, stannous sulfide has poor conductivity, severe volume expansion during battery charging and discharging, and will cause material pulverization. These shortcomings limit the application of stannous sulfide in lithium-ion negative electrodes.

[0003] Therefore, researchers first thought of combining tin sulfide and graphene in order to achieve a complementary effect. At present, the main methods for preparing tin sulfide / graphene materials are hydrothermal method and solvent thermal synthesis method. For example, S, N co-doped graphene composite SnS nanosheets were prepared by hydrothermal electrostatic self-assembly (ACS Appl. Mater. Interfaces 2019, 11, 44, 41363–41373 DOI: 10.1021 / acsami.9b14098); and SnS / graphene nanocomposites were prepared by simple solvent thermal synthesis using tin / graphene as precursors (Mater. Lett. 2017, 209, 338-341 DOI: 10.1016 / j.matlet.2017.08.054). However, both hydrothermal and solvent thermal synthesis methods have poor safety, high equipment requirements and are not suitable for mass production. In addition, the samples prepared by the above methods are all powders, and must be coated on copper sheets with a binder before being used as electrodes. The steps are cumbersome and not conducive to industrial production. In addition, the copper sheets also have an adverse effect on the performance of the battery to a certain extent. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a stannous sulfide / sulfur-nitrogen dual-doped graphene negative electrode material for improving the cycle performance and rate performance of a lithium-ion battery.

[0005] The technical solution for achieving the purpose of the present invention is as follows:

[0006] The preparation method of tin sulfide / sulfur-nitrogen dual-doped graphene negative electrode material comprises the following steps:

[0007] (1) According to the molar ratio of SnCl2·2H2O to thiourea of ​​1:20, the ethanol solution of SnCl2·2H2O was first dispersed in the ethanol solution of graphene oxide (GO), and then the ethanol solution of thiourea was added and stirred until the mixture was uniform;

[0008] (2) filtering the suspension obtained in step (1) and drying;

[0009] (3) The dried sample was heated to 650±100°C in a H2 / Ar mixed gas flow for thermal reduction treatment, and naturally cooled to room temperature to obtain tin sulfide / sulfur and nitrogen co-doped graphene anode material (SnS / 3DSNG).

[0010] Preferably, in step (1), the concentration of SnCl2·2H2O in the ethanol solution is 11.3 mg mL -1 .

[0011] Preferably, in step (1), the concentration of thiourea in the ethanol solution of thiourea is 30.4 mg mL -1 .

[0012] Preferably, in step (1), the concentration of the ethanol solution of graphene oxide is 1 mg mL -1 .

[0013] Preferably, in step (2), the drying temperature is 50 to 90° C. and the drying time is 3 to 12 hours.

[0014] Preferably, in step (3), the H2 content in the H2 / Ar mixed gas flow is 5%.

[0015] Preferably, in step (3), the heating rate is 10°C min -1 .

[0016] Preferably, in step (3), the thermal reduction treatment time is 2 to 3 hours.

[0017] The present invention also provides a tin sulfide / sulfur-nitrogen dual-doped graphene negative electrode material prepared by the above preparation method.

[0018] Furthermore, the present invention provides the use of the above-mentioned tin sulfide / sulfur and nitrogen dual-doped graphene negative electrode material in a lithium ion battery.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) Compared with the current traditional hydrothermal method for preparing tin sulfide / graphene materials, the present invention effectively combines tin sulfide and graphene by combining filtration and high-temperature calcination. The obtained sample has a three-dimensional flexible structure and improves the conductivity of the material. The tin sulfide / sulfur-nitrogen co-doped graphene can be directly used as an electrode material, saving costs.

[0021] (2) Thiourea provides a sulfur source and a nitrogen source. Through high-temperature calcination, SnS can be generated on the one hand, and graphene can be modified to prepare sulfur-nitrogen co-doped graphene on the other hand. SnS / sulfur-nitrogen co-doped graphene can not only effectively utilize the advantages of SnS's high theoretical capacity, but also increase the active sites in the material, thereby improving the electrochemical performance of the material. The SnS / sulfur-nitrogen co-doped graphene material of the present invention has a high electrochemical performance of 1A g -1 When the battery is charged and discharged under the current, the initial capacity reaches 1173mAh g -1 Even after 500 cycles, the battery capacity can still maintain 530mAh g -1 In the rate cycling test, the high current cycle returned to the initial 0.5A g -1 When cycling at low current, the battery capacity is still 503mAh g -1 The first pseudocapacitance of tin sulfide / sulfur-nitrogen co-doped graphene material as anode material for lithium-ion batteries is as high as 93.9%, with excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 SEM (a, b) and TEM images (c, d) of SnS / 3DSNG.

[0023] Figure 2 is the X-ray diffraction pattern of SnS / 3DSNG.

[0024] Figure 3 This is the X-ray photoelectron spectrum of SnS / 3DSNG.

[0025] Figure 4 Thermogravimetric images of SnS / 3DSNG (a), SnS / 3DSNG-1 (b) and SnS / 3DSNG-2 (c).

[0026] Figure 5 It is the cycle performance test chart of SnS / 3DSNG, SnS / 3DSNG-1 and SnS / 3DSNG-2 electrodes.

[0027] Figure 6 The current density is 0.5A g -1 , 1A g -1 , 2A g -1 , 3A g-1 , 5A g -1 and 0.5A g -1 Rate performance diagram of SnS / 3DSNG, SnS / 3DSNG-1 and SnS / 3DSNG-2 composite samples.

[0028] Figure 7 Pseudocapacitance contribution diagram of SnS / 3DSNG. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with specific embodiments and accompanying drawings:

[0030] Example 1

[0031] 0.226 g of SnCl2·2H2O and 1.52 g of thiourea (the molar ratio of SnCl2·2H2O to thiourea is 1:20) were dissolved in 20 mL and 50 mL of ethanol, respectively, and stirred for 0.5 h. Then, the SnCl2·2H2O solution was added to 80 mL of GO solution (concentration of 1 mg mL -1 ) and stirred and dispersed, and then the thiourea solution was added to the above mixture and stirred for 5 minutes. The mixed suspension was filtered and dried in a vacuum oven at 70°C for 8 hours. The dried sample was heated in a H2 / Ar (5% H2) mixed gas flow at a heating rate of 10°C min -1 The heat reduction treatment was carried out in a tube furnace, and the heating treatment was maintained for 2 hours after the temperature rose to 650°C. When the tube furnace was naturally cooled to room temperature, the obtained sample was named SnS / 3DSNG.

[0032] Comparative Example 1

[0033] 0.226 g of SnCl2·2H2O and 0.76 g of thiourea (the molar ratio of SnCl2·2H2O to thiourea is 1:10) were dissolved in 20 mL and 50 mL of ethanol, respectively, and stirred for 0.5 h. Then, the SnCl2·2H2O solution was added to 80 mL of GO solution (concentration of 1 mg mL -1 ) and stirred and dispersed, and then the thiourea solution was added to the above mixture and stirred for 5 minutes. The mixed suspension was filtered and dried in a vacuum oven at 70°C for 8 hours. The dried sample was heated in a H2 / Ar (5% H2) mixed gas flow at a heating rate of 10°C min -1 The heat reduction treatment was carried out in a tube furnace, and the heating treatment was maintained for 2 hours after the temperature rose to 650°C. When the tube furnace was naturally cooled to room temperature, the obtained sample was named SnS / 3DSNG-1.

[0034] Comparative Example 2

[0035] 0.226 g of SnCl2·2H2O and 1.14 g of thiourea (the molar ratio of SnCl2·2H2O to thiourea is 1:15) were dissolved in 20 mL and 50 mL of ethanol, respectively, and stirred for 0.5 h. Then, the SnCl2·2H2O solution was added to 80 mL of GO solution (concentration of 1 mg mL -1 ) and stirred and dispersed, and then the thiourea solution was added to the above mixture and stirred for 5 minutes. The mixed suspension was filtered and dried in a vacuum oven at 70°C for 8 hours. The dried sample was heated in a H2 / Ar (5% H2) mixed gas flow at a heating rate of 10°C min -1 The heat reduction treatment was carried out in a tube furnace, and the heating treatment was maintained for 2 hours after the temperature rose to 650°C. When the tube furnace was naturally cooled to room temperature, the obtained sample was named SnS / 3DSNG-2.

[0036] Table 1 Performance test results of tin sulfide / sulfur and nitrogen dual-doped graphene materials prepared in Examples and Comparative Examples

[0037]

[0038] Figure 1 The SEM and TEM images of SnS / 3DSNG. Figure 1 As can be seen in (a), the white particles are SnS nanoparticles, the black part is graphene, and SnS grows evenly on the graphene sheets. Figure 1 As can be seen in (b), the entire structure is composed of graphene nanosheets. The two-dimensional graphene sheets are stacked to form a good three-dimensional carbon skeleton to fix the SnS nanoparticles. The SnS particles are evenly distributed in the composite film and have a diameter of 20 to 50 nanometers. The SnS nanoparticles are interconnected after being encapsulated by graphene, which is beneficial to increase the conductivity of the material and improve the diffusion of lithium ions and the conduction of electrons. It is worth pointing out that this hierarchical three-dimensional sandwich structure is beneficial to constrain the volume expansion of the SnS nanoparticles in the graphene layer, inhibit the agglomeration of the SnS nanoparticles, and thus extend the cyclability of the battery. Figure 1 (c) It can be clearly seen that SnS nanoparticles with an average diameter of 20 to 50 nanometers are deposited on the graphene surface. Fast Fourier transform reveals that the SnS nanoparticles have (110) and (102) crystal planes. Figure 1 (d) It is confirmed that the SnS lattice fringes are about 0.298 nanometers, and it is confirmed that the SnS nanoparticles with good crystallinity have (110) crystal planes. It can also be seen from the figure that SnS is tightly wrapped by graphene to form a "sandwich" structure. This structure is conducive to preventing the shedding and agglomeration of SnS, shortening the distance of lithium ion and electron transmission, and buffering the volume expansion during the lithium ion deintercalation process.

[0039] Figure 2 The characteristic X-ray diffraction (XRD) pattern of SnS / 3DSNG. SnS / 3DSNG has peaks at (110), (120), (021), (101), (111), (040), (131), (141), (150), (211), (151), (160), (061), (042), (251) and (171), which are consistent with the peaks of SnS. The analysis of Jade 6.5 software shows that SnS has an orthorhombic structure. The peak at 2θ=20-30° is the characteristic diffraction peak of graphene, while the peak at 2θ=10-20° is the characteristic diffraction peak of graphene oxide. There is a peak next to the (120) peak that cannot be ignored. It is at 20-30° (marked with * in the figure). This peak is the characteristic diffraction peak of graphene. It shows that during the synthesis process, calcination at 650±100℃ not only reduces graphene oxide at high temperature, but also effectively compounds SnS nanoparticles and graphene together.

[0040] Figure 3 This is the X-ray photoelectron spectrum of SnS / 3DSNG. Figure 3 It can be seen that C, S, N, Sn and O exist in the SnS / 3DSNG material, which indicates that the S and N elements provided by thiourea are successfully doped into the SnS / 3DSNG material.

[0041] Figure 4 The thermogravimetric graphs of SnS / 3DSNG (a), SnS / 3DSNG-1 (b) and SnS / 3DSNG-2 (c). It can be seen from the figure that the graphene skeleton begins to decompose at around 400°C, and there is no weight loss after 600°C, so 600°C is selected as the carbonization temperature. The mass that remains unchanged after 600°C is the mass of SnS. This experiment regulated the proportion of SnS in SnS / 3DSNG, and found that with the increase of thiourea, the proportion of SnS finally generated also continued to increase. Among them, the maximum content of SnS in the regulation results is about 82.42wt.%, and the content of graphene is about 17.58wt.%.

[0042] Figure 5 The cycling performance test graph of SnS / 3DSNG, SnS / 3DSNG-1 and SnS / 3DSNG-2 electrodes. -1 The initial capacity of the battery during charge and discharge at a current density of 1173 mAh g -1 The initial capacities of SnS / 3DSNG-1 and SnS / 3DSNG-2 are 198 mAh g -1 , 698mAh g -1When the number of cycles reaches 500, the capacity of SnS / 3DSNG can still be stabilized at 572mAh g -1 At this time, the capacities of SnS / 3DSNG-1 and SnS / 3DSNG-2 electrodes are 70 mAh g -1 and 132mAh g -1 Obviously, the SnS / 3DSNG electrode can maintain the highest capacity and is the best performing electrode. This is because the graphene conductive skeleton provides a more effective electron channel on the one hand, and on the other hand, the structure of SnS and graphene can be cycled for a long time at this ratio, the structure is slowly destroyed and the advantage of the high theoretical capacity of SnS is efficiently utilized, thereby improving the material's deintercalation and extraction of lithium ions.

[0043] Figure 6 The current density is 0.5A g -1 , 1A g -1 , 2A g -1 , 3A g -1 , 5Ag -1 and 0.5Ag -1 The rate performance diagram of SnS / 3DSNG, SnS / 3DSNG-1 and SnS / 3DSNG-2 composite samples. It can be seen from the figure that the capacity of SnS / 3DSNG-1 electrode at the corresponding current density is 346 mAh g -1 , 213mAh g -1 , 145mAh g -1 , 104mAh g -1 , 28mAh g -1 , 228mAh g -1 The capacity of SnS / 3DSNG-2 electrode is 430 mAh g -1 , 320mAh g -1 , 204mAh g -1 , 105mAh g -1 , 69mAh g -1 , 282mAh g -1 The capacity of SnS / 3DSNG electrode at the corresponding current density is 820 mAh g -1 , 663mAhg -1 , 516mAh g -1 , 416mAh g -1 , 310mAh g -1 , 503mAh g -1 Compared with SnS / 3DSNG-1 and SnS / 3DSNG-2 electrodes, the initial capacity of SnS / 3DSNG electrode is the highest, even at 5A g -1Even when charged and discharged at a high current density, its capacity is still 310mAh g -1 In addition, the SnS / 3DSNG electrode returned to 0.5Ag after rapid charge and discharge with high current. -1 The initial current density is still as high as 503mAh g -1 The specific capacity of SnS / 3DSNG-1 and SnS / 3DSNG-2 electrodes far exceeds that of SnS / 3DSNG-1 and SnS / 3DSNG-2 electrodes. SnS / 3DSNG has the best rate performance. First, the SnS nanoparticles are evenly loaded on the graphene skeleton. Since graphene has extremely high flexibility, it is beneficial to alleviate the volume expansion of SnS during the charge and discharge process and maintain the integrity of the material structure. Second, sulfur and nitrogen doping improves the conductivity of the material and promotes the transmission of electrons. Third, SnS has the largest proportion in the SnS / 3DSNG electrode, so the amount of lithium ions inserted and extracted is correspondingly larger.

[0044] Figure 7 For SnS / 3DSND electrode, the scan rates were 0.2, 0.4, 0.6, 0.8, and 1 mV s -1 The black area in the figure directly reflects the capacity contribution of lithium-ion pseudocapacitance at high scan rates. As the scan frequency increases, the contribution rate of capacitance increases. -1 At a scan rate of 0.2 mV s -1 The pseudocapacitance contribution rate at the scan rate is still 74.8%, which shows that the capacity decay of the material is slow when it is cycled at high rates, and it can be charged and discharged quickly, which is consistent with the above-mentioned cycle and rate performance results. This is mainly due to the increase in the active mass of SnS and the increase in the number of S and N active sites in the material. In addition, the three-dimensional graphene structure can also buffer the volume expansion of the active material during the cycle, thereby maintaining the structural integrity of the material and achieving high-current fast charging.

Claims

1. A method for preparing a tin sulfide / sulfur-nitrogen dual-doped graphene negative electrode material, characterized in that: The following steps are involved: (1) According to the molar ratio of SnCl2•2H2O to thiourea of ​​1:20, the ethanol solution of SnCl2•2H2O was first dispersed in the ethanol solution of graphene oxide, and then the ethanol solution of thiourea was added and stirred until the mixture was uniform. The concentration of SnCl2•2H2O in the ethanol solution of SnCl2•2H2O was 11.3 mg mL −1 In the ethanol solution of thiourea, the concentration of thiourea is 30.4 mg mL −1 The concentration of graphene oxide in ethanol solution is 1 mg mL −1 ; (2) filtering the suspension obtained in step (1) and drying; (3) The dried sample is heated to 650±100°C in a H2 / Ar mixed gas flow for thermal reduction treatment, and naturally cooled to room temperature to obtain a tin sulfide / sulfur and nitrogen dual-doped graphene negative electrode material, wherein the H2 content in the H2 / Ar mixed gas flow is 5%.

2. The preparation method according to claim 1, characterized in that: In step (2), the drying temperature is 50-90° C. and the drying time is 3-12 hours.

3. The preparation method according to claim 1, characterized in that In step (3), the heating rate is 10°C min −1 .

4. The preparation method according to claim 1, characterized in that: In step (3), the thermal reduction treatment time is 2 to 3 hours.

5. A tin sulfide / sulfur-nitrogen dual-doped graphene lithium ion battery negative electrode material prepared according to the preparation method described in any one of claims 1 to 4.

6. Use of the tin sulfide / sulfur-nitrogen dual-doped graphene lithium ion battery negative electrode material according to claim 5 in a lithium ion battery.

Citation Information

Patent Citations

  • Composite cathode material for sodium battery and preparation method of composite cathode material

    CN105514356A

  • Preparation method for stannous sulfide / graphene compound photocatalyst

    CN106563469A

  • Sulfur-nitrogen dual-doped graphene nano material and preparation method and application thereof

    CN106684389A